CALCULATION OF OPERATION MODE OF OUTDOOR LIGHTING LINE WITH BILATERAL SUPPLY. Part 2 - V. B. Kozlovskaya; V. N. Kalechyts (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
The most important features of outdoor lighting lines are of considerable length and the use of a large number of light sources of an average power. Under such conditions, in order to determine and maintain the optimal modes of operation of outdoor lighting networks with a bilateral supply it is necessary to choose the wire section of the line. This section should provide the required voltage levels to the light sources in all modes, but it should not be too high, in order not to increase the cost of the grid. This article demonstrates an example of the choice of the optimum conductor cross-section of the lighting line when it is working in a normal mode (bilateral power supply) with voltage levels at the power items of 230 V, as well as in the mode of unilateral power (at voltage loss in the second power item) with a value of the voltage of 230 V in the first item of the power supply. The method of calculation of the mode of such a line that had been presented in part 1 of the article was used. The calculation is performed with the of MathCad software. The diagrams of the voltage distribution at items of the lighting line with bilateral power under conditions of different modes of functioning are plotted for various sections of aluminum conductors. The choice of the optimal values of the cross sections of the lighting network was based on the mentioned diagrams. The specific features of different modes of operation of the lighting line with the chosen conductor cross section were analyzed. Operating parameters for each phase of the line (i.e. voltage at the items of the circuit, power, currents, power loss and voltage drop in all sections) were determined. The presented data make one possible to estimate the power consumption of the lighting line taking the daily schedule of enabling and disabling of outdoor lighting networks into account. The most economical modes were determined.